TANTANGAN DAN INOVASI PEMBELAJARAN PAI PADA MASA PANDEMI COVID-19 - Eri Murniasih; Muhajir Muhajir (Journal of Research and Thought on Islamic Education (JRTIE), 2021)
Abstract: The Covid-19 pandemic has changed the order of learning, especially Islamic Religious Education (PAI), and presents its challenges for educators and students to quickly adapt the learning process from conventional to online internet-based learning or e-learning using various applications. This paper aims to examine what challenges and innovations in PAI learning are faced during the Covid-19 pandemic at the SMK Informatika in Serang City. The type of research used by the researcher is the descriptive qualitative research method. Data collection techniques using the research library and filling out questionnaires. The main data sources in this study were PAI subject educators and class XII students of SMK Informatika Serang and some literature. The results and conclusions in this study are: (a) SMK Informatika answers the challenges of online learning by creating an E-Learning application for SMK Informatika. (b) Educators and students at SMK Informatika agree that the role of teachers cannot be replaced by technological sophistication, especially PAI teachers who are tasked with shaping the character of students. (c) PAI educators in SMK Informatika innovate to conduct online and offline meetings regularly to inculcate character as the main goal of PAI (Blended Learning). (d) Family, Community, and Educators are the three main pillars of education, synergizing, supporting each other and their roles cannot be separated so that the main goal of PAI learning, namely character building, can be achieved even though learning is carried out online.Keyword: Challenges, Covid-19 Pandemic, Innovation, PAI Learning